ADOLESCENT COUNSELING ON THE IMPACT OF EARLY MARRIAGE TOWARDS MOROREJO VILLAGE FREE FROM STUNTING - Sinduwiatm, Kukuh; Herista, Nasya Avrilia; Aprilina, Adelia Avita (Journal of Learning on History and Social Sciences, 2025)
Objective: Early marriage remains a phenomenon that is quite high in Pasuruan Regency, including in Mororejo Village, Tosari District. This condition has serious implications for reproductive health, education, as well as the risk of stunting in children. Through community service activities (Abdimas), counseling was conducted for adolescents with the aim of increasing understanding of the impact of early marriage as well as supporting the realization of Mororejo Village free from stunting. Method: The method used was interactive lectures, group discussions, and role play accompanied by pre and post activity evaluations. Results: The results showed a significant increase in adolescent knowledge, where previously 65% of participants did not understand the relationship between early marriage and stunting, then after counseling more than 85% were able to explain the impact well. In addition, there was a positive change in attitude, shown by the commitment of adolescents to delay the age of marriage and increase attention to reproductive health. Novelty: This activity proves that an educative-participatory approach is effective in increasing adolescents’ critical awareness and can be a strategy to prevent early marriage as well as reduce stunting rates in Mororejo Village.